PENGARUH VARIASI BENTUK BRIKET ARANG BIOMASSA BERBAHAN LIMBAH KAYU TERHADAP NILAI KALOR DAN BOILING TIME : THE EFFECT OF VARIATIONS IN THE SHAPE OF BIOMASS CHARCOAL BRIQUETTES MADE FROM WOOD WASTE ON CALORIFIC VALUE AND BOILING TIME - I Wayan Joniarta; Zohimundin Usman; Made Wijana; I Kade Wiratama (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2025)
Most Indonesian people currently use energy derived from fossil fuels, such as fuel oil, gas and coal. The impact of using fossil fuels is that it can damage the environment. Several alternative energy sources that are commonly developed are biomass energy. This biomass is usually processed into biochar which is a fuel with a high calorific value and can be used in everyday life. Briquettes are an energy source derived from biomass which can be used as alternative energy. In this study, briquettes were made from teak, acacia and mahogany wood waste. The method used is an experiment with the carbonization process using a modified composing drum. The independent variables used were briquette materials from teak, acacia and mahogany wood waste, variations in the shape of cube, cylindrical and hexagonal jerry cans. Tests include analysis of water content, calorific value, and changes in temperature. The results of this study showed that the best moisture content was obtained from cylindrical teak wood waste briquettes with an average value of 3.57%. Then for the calorific value, the best results were obtained from cylindrical teak wood waste briquettes with a value of 3457.0 Kkal/kg. and for temperature changes the best results were obtained on the cube-shaped mahogany wood waste briquette specimens with an average value of 10 minutes 46 seconds.